Gains Across WHO Dimensions of Function After Robot-Based Therapy in Stroke Subjects. (December 2020) - Wu, Jennifer; Dodakian, Lucy; See, Jill; Burke Quinlan, Erin; Meng, Lisa; Abraham, Jeby; Wong, Ellen C.; Le, Vu; McKenzie, Alison; Cramer, Steven C.
Background: Studies examining the effects of therapeutic interventions after stroke often focus on changes in loss of body function/structure (impairment). However, improvements in activities limitations and participation restriction are often higher patient priorities, and the relationship that these measures have with loss of body function/structure is unclear. Objective: This study measured gains across WHO International Classification of Function (ICF) dimensions and examined their interrelationships. Methods: Subjects were recruited 11 to 26 weeks after hemiparetic stroke. Over a 3-week period, subjects received 12 sessions of intensive robot-based therapy targeting the distal arm. Each subject was assessed at baseline and at 1 month after end of therapy. Results: At baseline, subjects (n = 40) were 134.7 ± 32.4 (mean ± SD) days poststroke and had moderate-severe arm motor deficits (arm motor Fugl-Meyer score of 35.6 ± 14.4) that were stable. Subjects averaged 2579 thumb movements and 1298 wrist movements per treatment session. After robot therapy, there was significant improvement in measures of body function/structure (Fugl-Meyer score) and activity limitations (Action Research Arm Test, Barthel Index, and Stroke Impact Scale–Hand), but not participation restriction (Stroke Specific Quality of Life Scale). Furthermore, while the degree of improvement in loss of body function/structure was correlated with improvement in activity limitations, neither improvement in loss of body function/structure nor improvement in activity limitations was correlated with change in participation restriction. Conclusions: After a 3-week course of robotic therapy, there was improvement in body function/structure and activity limitations but no reduction in participation restriction.